Endoplasmic Reticulum Stress‐Induced triggering Receptor Expressed on Myeloid Cells 2 (TREM2) Downregulation Exacerbates Platelet Activation and Myocardial Infarction in Patients With Coronary Artery Disease - Xiaowen Wu; Guanxing Pan; Lin Chang; Qian Liu; Yangyang Liu; Wei Zhang; Yifan Guo; Ge Zhang; Haoxuan Zhong; Zhiyong Qi; Jianjun Zhang; Ruyi Xue; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Coronary artery disease is characterized by chronic immune‐inflammation, excessive endoplasmic reticulum (ER) stress, and platelet hyperactivity; however, whether there is a signaling hub linking these events remains unclear. Here, we identified that TREM2 (triggering receptor expressed on myeloid cells 2), an important pattern recognition receptor of the innate immune system, may serve as one such hub. Methods TREM2 expression and ER stress were assessed in platelets. Transcriptional repression of TREM2 by excessive ER stress was evaluated using luciferase assay, chromatin immunoprecipitation, and electrophoretic mobility shift assay. The effects of TREM2 deficiency on platelet function, mouse FeCl3‐induced mesenteric arterial thrombosis, and myocardial infarction were explored. A TREM2‐activating antibody was also evaluated for its antiplatelet, antithrombotic, and cardioprotective potential against myocardial infarction. Results We found that platelets express TREM2, and its expression is reduced in platelets from patients with coronary artery disease. Excessive ER stress downregulated TREM2 through the CHOP (C/EBP‐homologous protein)‐C/EBPα axis. TREM2 deficiency enhanced platelet activation in response to adenosine diphosphate, collagen, and CRP (collagen‐related peptide). TREM2 deficiency exacerbated mouse mesenteric arterial thrombosis and aggravated experimental myocardial infarction. Furthermore, a TREM2‐activating antibody inhibited platelet activation, reduced thrombosis, and alleviated experimental myocardial infarction. Mechanistically, the TREM2/DAP12 (DNAX activating protein of 12 kDa)/SHIP1 (Src homology 2 domain‐containing inositol 5‐phosphatase) axis negatively regulated platelet activation through reducing phosphatidylinositol (3,4,5)‐trisphosphate levels and inhibiting Akt phosphorylation. Sphingosine‐1‐phosphate was identified as a physiological TREM2 agonist. Conclusions TREM2 integrates ER stress, immune inflammation, and platelet function. ER stress‐induced TREM2 downregulation contributes to platelet hyperactivation in coronary artery disease, suggesting TREM2 activation as a novel therapeutic target.